The Role of the Alliance of Independent Journalist (AJI) Palembang in Dealing with Hacking and Disinformation of Journalist - Tuti Inayah (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
In the midst of the rampant hacking and disinformation efforts of journalists. The Alliance of Independent Journalists (AJI) Palembang continues to work on preventing hacking and disinformation, with the dynamics of rapid information transformation. Professional journalists are demanded not to get caught up in disinformation. The challenge of dealing with this problem is getting tougher when the onslaught of social media (Medsos) occurs. Social media is a public space for exchanging opinions and information which is very popular at this time. This is a challenge for the Alliance of Independent Journalists (AJI) Palembang in determining the initial steps that must be taken in the role of preventing and protecting journalists who have experienced hacking and disinformation. Researchers used qualitative methods through documentation, observation and interview approaches. From the results of the research that has been done, it can be concluded that the role of AJI in dealing with hacking and disinformation is through the workings of the press. This step is consistently carried out by AJI considering that hacking and disinformation are also often used to undermine press freedom or the credibility of press freedom defenders. AJI's goal is none other than to support a healthy information ecosystem for the public. In accordance with the Press Law number 40 of 1999, journalists have freedom in carrying out journalistic work. So there must be efforts of terror and silencing. Any physical or non-physical attacks and disinformation efforts cannot be justified. AJI sharply condemned these steps. In addition, AJI also provides digital security training and seeks to advocate for every journalist affected by digital attacks or disinformation for legal settlement.